2001
DOI: 10.1104/pp.126.2.759
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Accumulation of Phosphatidylinositol 4,5-Bisphosphate and Inositol 1,4,5-Trisphosphate Correlates with Calcium Mobilization in Salt-Stressed Arabidopsis

Abstract: The phosphoinositide phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] is a key signaling molecule in animal cells. It can be hydrolyzed to release 1,2-diacyglycerol and inositol 1,4,5-trisphosphate (IP 3 ), which in animal cells lead to protein kinase C activation and cellular calcium mobilization, respectively. In addition to its critical roles in constitutive and regulated secretion of proteins, PtdIns(4,5)P 2 binds to proteins that modify cytoskeletal architecture and phospholipid constituents. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
263
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(273 citation statements)
references
References 54 publications
6
263
0
4
Order By: Relevance
“…Inositol 1,4,5-triphosphate (IP3) acts as a secondary messenger in signal transduction pathways involving cytosolic Ca 2+ elevations in plants (29). In these signaling pathways, cytosolic IP3 generation on perception of an external stimulus leads to cytosolic Ca 2+ elevation because of activation of IP3-sensitive tonoplast-localized Ca 2+ channels (30); the resulting cytosolic Ca 2+ spike occurs because of release of intracellular Ca 2+ stores.…”
Section: His-gchismentioning
confidence: 99%
“…Inositol 1,4,5-triphosphate (IP3) acts as a secondary messenger in signal transduction pathways involving cytosolic Ca 2+ elevations in plants (29). In these signaling pathways, cytosolic IP3 generation on perception of an external stimulus leads to cytosolic Ca 2+ elevation because of activation of IP3-sensitive tonoplast-localized Ca 2+ channels (30); the resulting cytosolic Ca 2+ spike occurs because of release of intracellular Ca 2+ stores.…”
Section: His-gchismentioning
confidence: 99%
“…Excess Na + -induced membrane depolarization may activate mechanosensitive Ca 2+ channels to generate Ca 2+ signature under salt stress (4,17). Pharmacological studies and genetic analysis have shown the involvement of inositol 1,4,5-tris phosphate (IP 3 )-gated Ca 2+ channels in the regulation of Ca 2+ signature during salt stress (24)(25)(26). The FRY1 locus of Arabidopsis encodes an inositol polyphosphate 1-phosphatase, which catabolizes IP 3 .…”
Section: Second Messengersmentioning
confidence: 99%
“…12 Important roles of PLC in plant cell responses to hyperosmotic stress and drought in different plant systems are well documented. 13,14 The PLC/DAGK-derived PA also seems to be the prominent species involved in biotic stress tolerance. Thus, tomato cell suspensions responded to a number of pathogenic elicitors by increasing their PA contents within minutes of elicitation, which arose mostly via DAG phosphorylation and was correlated with decreased levels of PtdIns(4,5)P 2 .…”
Section: Introductionmentioning
confidence: 99%